Study of the Therapeutic Effect of Cytokine-Preconditioned Mesenchymal Stem Cells and Their Exosomes in a Mouse Model of Psoriasis - Dairov, Aidar; Issabekova, Assel; Sarsenova, Madina; Sekenova, Aliya; Shakhatbayev, Miras; Alimbek, Symbat; Kudaibergen, Gulshakhar; Nurkina, Assiya; Akhmetollayev, Ilyas; Kang, Kyung-Sun; Ogay, Vyacheslav (Eurasian Journal of Applied Biotechnology, 2025)
Psoriasis is a chronic inflammatory skin disease sustained by a cytokine-rich microenvironment that perturbs keratinocyte-immune crosstalk. Mesenchymal stem cells (MSCs) and their exosomes offer a cell-free route to immunomodulation, but basal preparations can be variably potent. We asked whether disease-informed priming of human umbilical cord blood MSCs with psoriasis- relevant cytokines would reprogram paracrine output and generate exosomes with stronger anti- inflammatory activity in vitro. Across multiple priming conditions, MSCs adopted a pro-resolving secretory profile characterized by higher levels of canonical mediators (including prostaglandin E2 and TGF-β1) and a coordinated upshift in immunoregulatory genes associated with tolerance, tissue protection, and resolution (such as IDO, iNOS, COX-2, TSG-6, IL-10, HGF, and galectin- 1). These molecular changes translated into function: compared with exosomes from unprimed MSCs, primed MSC exosomes more effectively dampened inflammatory signaling in stimulated target cells, reduced the release of pro-inflammatory cytokines, and preserved markers of barrier- relevant homeostasis in keratinocyte models. The most consistent gains were observed when MSCs were exposed to a combinatorial cytokine milieu that mirrored the psoriatic niche, yielding exosome preparations that coupled robust bioactivity with stable size distribution and expected vesicle markers. Together, the in vitro data show that a tractable priming step can tune MSC paracrine biology and produce exosomes with superior immunomodulatory performance without increasing manufacturing complexity. Preliminary in vivo observations in an imiquimod-induced mouse model aligned with the in vitro potency ranking, providing orthogonal biological support while keeping the emphasis on rigorous cell-based readouts. We demonstrated that disease- relevant priming enhances the anti-inflammatory capacity of MSC-derived exosomes in psoriasis and other cytokine-driven dermatoses. Acknowledgement: We thank our colleagues, institutional core facilities, and animal-care staff for their invaluable technical support and resources that made this study possible. Keywords: mesenchymal stem cell, exosome, psoriasis References: Hawkes, J.E., Yan, B.Y., Chan, T.C. & Krueger, J.G. Discovery of the IL-23/IL-17 signaling pathway and the treatment of psoriasis. J. Immunol. 201, 1605-1613 (2018). Griffiths, C.E.M., Armstrong, A.W., Gudjonsson, J.E. & Barker, J.N.W.N. Psoriasis. Lancet 397, 1301–1315 (2021). Nestle, F.O., Kaplan, D.H. & Barker, J. Psoriasis. N. Engl. J. Med. 361, 496-509 (2009). Zhang, B., Lai, R.C., Sim, W.K., Choo, A.B.H., Lane, E.B. & Lim, S.K. Topical application of mesenchymal stem cell exosomes alleviates the imiquimod-induced psoriasis-like inflammation. Int. J. Mol. Sci. 22, 720 (2021). Alvites, R., Branquinho, M., Sousa, A.C., Lopes, B., Sousa, P., Magalhães, F., Moura, C., Atayde, L.M., Santos, J. & Maurício, A.C. Mesenchymal stem/stromal cells and their paracrine activity- Immunomodulation mechanisms and how to influence the therapeutic potential. Pharmaceutics 14, 381 (2022). Tang, Y., Zhou, Y. & Li, H.J. Advances in mesenchymal stem cell exosomes: A review. Stem Cell Res. Ther. 12, 71 (2021).